Effect of parameters on the quality of core‐shell fibrous scaffold for retinal differentiation of conjunctiva mesenchymal stem cells. Issue 1 (27th September 2016) - Nadri, Samad; Nasehi, Fatemeh; Barati, Ghasem
Abstract: This article describes the coaxial electrospinning to generate core‐shell fibers from polycaprolactone (PCL) and polyethylene glycol (PEG) for differentiation of conjunctiva mesenchymal stem cells (CJMSCs) into photoreceptor‐like cells by delivery of taurine. Also, the effects of many parameters such as polymer concentration, nozzle collector distance, applied voltage, and outer solution flow rate on creation of the core‐shell structure were examined. The morphology and structure of fibers were characterized using scanning, transmission electron microscopy, and fourier transform infrared spectroscopy and then retinal differentiation was examined by quantitative real time PCR (qPCR). Significant variations between 25% and 35% PEG concentration groups for fiber diameter were documented. As faster flowing rates from the outer nozzle (PCL fluid) were applied, the creation possibility of fibrous scaffold was increased. The lowest diameter and the best quality alignment of core‐shell fibrous scaffold were achieved in 22 Kv and 24 Kv. As rising distancing were applied, the fibrous diameter increased and spraying was observed. qPCR analysis demonstrated the differentiation of CJMSCs to photoreceptor like cells on PEG/PCL scaffolds. According to the result, we have proved successful in the creation of core/shell fibrous scaffold of PEG/PCL by coaxial electrospinning for retinal tissue engineering. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 189–197, 2017.